New additions to the Chinese Anelytra Redtenbacher, 1891 (Tettigoniidae: Conocephalinae; Agraeciini) - Liu, Jing; Yang, Zizhong; Lu, Xiangyi; Bian, Xun (Zootaxa, 2021)
This paper describes three new species from Yunnan Province and provides morphological characters of Anelytra multicurvus Shi & Qiu, 2009 and Anelytra (Euanelytra) adjacens soror Gorochov, 1994. And two mitogenomes of Anelytra are reported. All the specimens are deposited in Guangxi Normal University and Institute of Entomoceutics Research, Dali University.